The Influence of Ming Dynasty Buddhism’s Chan Jing He Yi (Integration of Zen and Pure Land Buddhism 禪淨合一) on Buddhist Thought in Journey to the West - Ran Wei (Religions)
In the mid-to-late Ming Dynasty, Yunqi Zhuhong 雲栖祩宏 and Ouyi Zhixu 蕅益智旭 integrated Zen thought and Pure Land Buddhism based on the fusion of various Buddhist sects, which facilitated the transition to Chan Jing He Yi (integration of Zen and Pure Land Buddhism 禪淨合一). In this context, Journey to the West 西遊記, published in the late Ming Dynasty, reflects the characteristic of Chan Jing He Yi (integration of Zen and Pure Land Buddhism 禪淨合一). Based on the historical fact that the monk Xuanzang 玄奘 journeyed to India to seek Buddhist scriptures during the Tang Dynasty’s Zhenguan period, four relatively complete literary works that recount the stories of this westward journey were published over nearly a thousand years, from the Tang Dynasty to the Ming Dynasty: Da Ci En Si San Zang Fa Shi Zhuan 大慈恩寺三藏法師傳, Da Tang San Zang Qu Jing Shi Hua 大唐三藏取經詩話, the Journey to the West drama 西遊記雜劇, and Journey to the West. The Buddhist ideas in these four works went through a transformation from advocating yoga theory 瑜伽論 to advocating belief in Vaisravana 毗沙門天王信仰 and then to focusing on the “mind nature 心性” theory of Zen Buddhism. Finally, in Journey to the West, Buddhist thought is aimed at achieving rebirth in the Western Pure Land and supplemented with Chan Buddhist practices, which are aligned with the trend of Chan Jing He Yi (integration of Zen and Pure Land Buddhism 禪淨合一). In Journey to the West, the concepts of Ming Xin Jian Xing (find one’s true self 明心見性) and Ji Xin Ji Fo (the mind is the Buddha 即心即佛) differ from the Zen Buddhism concept of seeing one’s own nature. Instead, it requires seeking other Buddhas and ascending to the Western Pure Land to meet Amitabha Buddha in order to achieve complete spiritual cultivation. This had changed from the Wei Xin Jing Tu (mind-only Pure Land 唯心淨土) theory advocated by Zen Buddhism to the Xi Fang Jing Tu (Western Pure Land 西方淨土) theory advocated by the Pure Land School. The numerous depictions of Pure Land cultivation methods, such as Cheng Ming Nian Fo (chanting the name of Amitabha Buddha 稱名念佛), Chi Jie (commandment keeping 持戒), and the Pure Land reincarnation-type Guanyin faith 淨土往生型觀音信仰, also appear in Journey to the West, reflecting the profound influence of Chan Jing He Yi 禪淨合一 in the mid-to-late Ming Dynasty on Journey to the West.